Wedding Ritual Mompi’ohupi: Semiotics Approach - Marshanda Anggraeni; Sintia; Novi Dwi Kencana Hipan; Siti Rachmi; Nurlaela (Universitas Veteran Bangun Nusantara Sukoharjo, 2026)
This study examines Mompi’ohupi wedding ritual practiced by Saluan community in Batui, Banggai Regency, Central Sulawesi. Its tradition is deeply embedded in semiotic meanings and meticulously preserved to this day. The documentation scarcity and inadequate comprehension of the cultural symbols embodied in the ritual raise concerns about the potential erosion of cultural identity in the face of modernization. In this study, it aims to identify and analyze semiotic meanings of the signs within the ritual by applying Peirce’s theoretical framework. A qualitative research design was employed, with data collected through in-depth interviews and documentation involving traditional leaders and community members. The findings reveal that each element of the ritual including tampok leaves, puring flowers, popoloti leaves, pupur, suhangbalu grass, white rice, lamps, an umbrella, and doda leaves carries symbolic values representing purity, protection, harmony, prosperity, and spiritual enlightenment. This study contributes to preservation of local cultural heritage, enriches scholarly discourse in anthropology and semiotics, and put more sustainable efforts into protecting traditional practices amid the dynamics of globalization.